Turcogammarus aralensis (Uljanin, 1875), a relict pontogammarid amphipod crustacean from the Aralo-Caspian paleobasin: redescription, phylogenetic position and biogeography - Copilaș-Ciocianu, Denis; Sarmanov, Aibek; Sergaliyev, Nurlan; Sidorov, Dmitry (Zootaxa, 2022)
The Ponto-Caspian region harbours the world’s second most diverse lacustrine radiation of amphipod crustaceans. The taxonomic position of some of these species is unclear, due to incorrectly defined species limits, poor descriptions, and in some cases, poorly understood characters, such as armament of dorsal integuments. A pertinent example is Turcogammarus aralensis (Uljanin, 1875), which inhabits the Aral Sea and adjacent water bodies like the brackish lake Shalkar (Charkhal), lower reaches of the Syr Darya and Volga, and extends ca. 2500 km westwards in the Black Sea basin. This species has never been properly described, which has led to frequent taxonomic reshuffling. Herein, we provide a full re-description, ascertain its phylogenetic position using the cytochrome c oxidase subunit I (COI) marker, and review its geographical distribution. Our molecular analyses reveal T. aralensis as a sister species to the widespread Obesogammarus crassus (Sars, 1894), and its species status was further confirmed by three molecular species delimitation methods. Turcogammarus aralensis and O. crassus share many similarities such as the setation of the antennae and pereopods 3–4, and poorly setose posterior margin of pereopod 7 basis. Further study is needed to ascertain the validity of the genus Turcogammarus.